Expert System for Diagnosing Diseases in Tomato Plants Using a Website-Based Forward Chaining Method : Sistem Pakar Mendiagnosa Penyakit pada Tanaman Tomat menggunakan Metode Forward Chaining Berbasis Website - Roni, Katrina Rambu Bangi; Hariadi, Fajar (JOINCS (Journal of Informatics, Network, and Computer Science), 2022)
Tomato plant is one of the plants in agriculture that is widely cultivated in Indonesia, one of which is in East Sumba Regency. The problem that is often faced is the lack of knowledge and facilities for tomato farmers which are still limited in dealing with diseases in these tomatoes. To diagnose tomato plant diseases that attack through the symptoms they cause, a tomato plant expert is needed to analyze and diagnose. Currently farmers often ignore tomato diseases due to lack of knowledge. They assume it's finally happening in the planting phase, tomato pest and disease experts are reduced, they don't know how to control and eliminate decreased productivity. In this case, to help farmers know the type of disease that attacks, an expert system is needed to help diagnose tomato plant diseases and provide the right solution in handling the disease using the Forward Chaining method. In the Forward Chaining method, the data search process starts from the premise to the final conclusion. Based on the test results, it can be seen that the probability value for the accuracy of the expert system produced is capable of having a percentage of 100%, from the calculation of the 8 types of the same disease, for inaccuracy so that this expert system can be stated to have been running well.